Lupus Miliaris Disseminatus Facei: An uncommon cause of Non-infectious granulomatous dermatitis - Dr. Nadia Shirazi; Dr. Rashmi Jindal (Tropical Journal of Pathology and Microbiology, 2019)
Cutaneous granulomatosis (Infectious and non-infectious) are a heterogeneous group of diseases, characterized by an inflammatory skin reaction triggered by a wide variety of stimuli, including infections, foreign bodies, malignancy, metabolites, and chemicals. We present here a rare case of multiple caseating granulomas on face of a young man who was clinically suspected to be sarcoidosis however diagnosed as Lupus Miliaris Disseminatus Facei on biopsy.